PUTEREA CUVÂNTULUI SACRU CONFRUNTAT CU INDIVIDUALISMUL ȘI EXTREMISMUL PROGRESIST COTIDIAN (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
The power of the Sacred Word confronted with everyday progressive individualism and extremism.The word is the basis of the vocabulary by which we express ourselves in our relationships with our fellow human beings and with God. Man expresses his thoughts and will through speech and writing. Man expresses his feelings and emotional states through articulated words, signs, attitudes and movements. People feel the need to communicate through articulate language. Man, through the intellectual and spiritual function of thought, has the possibility of expressing himself consciously through speech, being able to transform his thoughts into words, into articulated sound. Because of the possibility of expressing his thought in words, man is a being superior to all other living beings; he speaks by thinking and thinks by speaking. Because man was created by God with brain structures capable of transforming the language of thought into articulate language, speech becomes the superior product of the human brain. Speech is a priceless gift of God which man enjoys in life, through which he can express his thoughts and feelings, the expression of his conscience, work, create, develop his intelligence, his memory, become master over the earth and its creatures, manage, utilize and transform what God has entrusted to him on earth. Thanks to verbal communication human life and social life became possible. Through this gift of God, man has been able to capitalize it in countless words, words of love, words of longing, words of encouragement, words of comfort, words of praise and praise to God, words of success, words of brotherhood, words of work and creation. Christian rhetoric must adapt to the times in order to withstand the onslaught of progressive atheism. Today’s education and religious pluralism face daily individualism and extremism, which is why rhetorical pregrammatism is needed to nurture, mold, and shape strong character individuals in a holistic world increasingly distant from God. Religious pluralism in modern society presupposes the existence of several religious traditions and is associated with other areas, such as cultural pluralism, ideological pluralism, political pluralism or ethnic pluralism. One of the values of today’s education and religious pluralism is the tolerance of genuine dialog, in which people not only adopt a tolerant and active attitude in understanding others, but also give those with whom they disagree the same respect that they themselves hope to receive. In this context, oratorical discourse has a duty to create bridges of dialog between people of different confessions, social positions, economic situations or heterogeneous political views.